Training on Processing Banana Peel Waste into Eco-enzyme and Eco-enzyme Soap to Implement Zero Waste in Kunjir Tourism Village - Asep Sukohar; Dwi Aulia Ramdini; Citra Yuliyanda Pardilawati; Afriyani Afriyani; Nurhayati Nurhayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Eco-enzyme is one of the solutions for waste organic management to become a higher-value product. As a tourist village, Kunjir village is one of the banana producers, where it needs help with garbage or banana waste from plantations. This waste can damage beauty and pollute the environment. Therefore, this engagement in community activity in waste organic management from banana peels is necessary to implement zero waste and a healthy environment. We aimed to improve the knowledge and skills of the local community in waste management. Banana peels become eco-enzyme and soap that contains eco-enzyme products. The eco-enzyme information was delivered first and then followed by practice or simulation. Twenty-five respondents were dominated by household wives, with ages 31-40 years as much as 36%, 41-50 years 28%, 51-60 years 25%, and 21-30 years 12%. According to the measurement of the initial score, 48% of respondents have good knowledge, and 92% have improved after following the training. We conclude that 44% of the total score of respondents was improved. Through this training, it is hoped that we can improve banana waste processing and improve our skills in processing eco-enzyme organic waste into a liquid rich in benefits, especially as a cleaning agent. This activity is essential in initiating waste management and implementing a healthy environment. Furthermore, it can encourage self-resilience and the development of a tourist village.